Corpus based analysis of established preposition-noun word combinations with the meaning of emotions (aus Spaß = for fun, aus Lust = for pleasure, aus Angst = from fear...) - Banášová, Monika Hornáček; Fraštíková, Simona; Ješíková, Mária; Baghana, Jerome (Linguistics and Culture Review, 2021)
Corpus linguistics is used in this paper to describe selected established German-language combinations firmly connecting prepositions and nouns (German: Substantiv) with a zero article, a sign of their lexicalisation. The focus is on preposition-noun combinations that express emotions in a primarily causal adverbial function, such as aus Angst ‘from fear’, aus Furcht ‘for fear’; aus Spaß ‘for fun’, aus Lust ‘for pleasure’ aus Verzweiflung ‘out of desperation/despair’, aus Frust ‘out of frustration’. The paper points out the insufficient lexicographic description currently available in dictionaries, while emphasising that the meaning of the word combination can only be analysed in context and, from their typical occurrence, it is possible to distinguish several aspects of the combination used, something dictionaries usually do not reflect. Research into these word combinations constitute a desideration of contemporary linguistics.